Impact of Scientific Agricultural Technologies on Livelihood Security of Tribal Farmers in Assam - Sharma, Haridra; Mishra, Prasanta (International Journal of Economic Plants, 2024)
The study was conducted during December, 2019 to December, 2021 at Assam Agricultural University, Jorhat, Assam, india with an objective to examine the impacts of scientific agricultural technologies on tribal livelihood security. Ex-post-fact research design was adopted to collect data from 400 tribal farmers from four tribal dominated districts viz., Chirang, Kokrajhar, Dhemaji and Karbi Anglong of Assam. Impacts weremeasured in terms of Livelihood Security Index (LSI) and Livelihood Endowment Status (LES) developed by Abadi (2010). When assessed on the basis of LSI, overall 31.00% shift was observed in case of beneficiary tribal farmers on before and after basis. LES was assessed comparing the beneficiary tribal farmers with non-beneficiary tribal farmers and the data revealed significant difference of 26.00% between the two groups. However, it was evident from the investigation that time gap in input supply, non-availability of suggested inputs locally after project period, high cost of inputs, lack of own capital to maintain the enterprises, difficulty in maintaining accounts etc. were the foremost problems faced by majority of the respondents.